Intracranial myeloid sarcoma presentation in distant acute myeloid leukemia remission. (July 2021) - Lee, Dennis; Omofoye, Oluwaseun A.; Karnati, Tejas; Graff, John Paul; Shahlaie, Kiarash
Highlights: Intracranial myeloid sarcoma is a rare central nervous system manifestation of hematopoietic neoplasms of myeloid origin. Intracranial myeloid sarcoma most commonly presents in association with acute myeloid leukemia. Goals of neurosurgical intervention should be symptomatic relief of mass effect and pathological diagnosis. Intracranial myeloid sarcoma is exquisitely sensitive to adjuvant radiation and medical management. Abstract: Intracranial myeloid sarcoma (IMS) is a rare central nervous system manifestation of hematopoietic neoplasms of myeloid origin. We report the first case of IMS treatment with an isocitrate dehydrogenase-2 (IDH-2) inhibitor, Enasidenib, following surgical resection, whole-brain radiation, and consolidation Etoposide/Cytarabine therapy. A 42-year-old female was diagnosed with IMS after a 10-year remission of her acute myeloid leukemia (AML). She underwent surgical debulking and had postoperative resolution of her visual symptoms. She received adjuvant radiation and medical management, and continues to show no evidence of recurrence or progression at 17 months postoperatively. This case is notable for an isolated IMS presentation in a patient with a very distant history of AML remission, and without evidence of concurrent bone marrow relapse. The goals of neurosurgical intervention should be symptomatic relief of mass effect and pathological diagnosis, due to the sensitivity of IMS to adjuvant radiation and medical management such as IDH-2 inhibitors.